Does the Gram-negative Bacteria Colonization Impact on the Risk of Develop Infection by Those Organisms During Neutropenia?. (4th October 2017) - Romi, Renata P; Freire, Maristela; Bittencourt, Driele P; Bonazzi, Patricia Rodrigues; Hatanaka, Veruska M.A; Ibrahim, Karim Y; Diz, Maria Del Pilar E; Hoff, Paulo Mg; Abdala, Edson; Pierrotti, Ligia C
Abstract: Background: The febrile neutropenia (FN) is a common morbidity among cancer patients and effective initial antimicrobial therapy is associated to low mortality. Methods: The aim of this study was to analyze the impact of colonization by multidrug-resistant Gram-negative bacteria (MDRGNB) in risk of developing MDRGNB infection during a neutropenia period. We retrospectively assessed all patients that came to the hospital with FN from July 2012 to September 2016. We performed a matched case–control study. Case was defined as a patient with FN and positive blood culture for ESBL-producing Enterobacteriaceae or carbapenem-resistant GNB. For each case, two controls were chosen and were paired by period of hospitalization, one of them with positive blood culture by sensitive bacteria and the other one without an isolated agent. Independent variables analyzed were related to patient characteristics, MDRGNB colonization and FN features. Statistical analysis was performed for univariate analysis by McNemar's chi-square or Wilcoxon test and for multivariate analysis by conditional logistic regression. Results: A total of 21 cases and 42 controls were analyzed. Hematological malignancies were present in 24 (38.1%) patients. The most common agent isolated in FN from the above cases was ESBL-producing E . coli (6–27.3%), followed by carbapenem-resistant K. pneumoniae (5–22.7%). The majority of FN had no site was identified; the most common site among cases was pneumonia (7–33.3%). Overall 15 (23.8%) patients were colonized by MDR GNB on hospital admission, among those 6 developed infection by the same agent by which he/she was colonized. The only risk factor for bacteremia by MDR GNB identified in multivariate analysis was previous MDRGNB colonization (OR 6.19 P = 0.007). Overall 30-day mortality rate was 30.2% in controls vs. 81.0% in patients with bacteremia by MDRGNB ( P = 0.02). Conclusion: Colonization by MDRGNB increases the risk of infection by those agents during neutropenia period and MDRGNB infection is associated with a higher mortality compared with those with non-MDRGNB infection. Disclosures: All authors: No reported disclosures.